A cohort study of prolactin and non-puerperal mastitis using real world data - Yulian Yin; Haoxin Le; Yifan Cheng; Yuanyuan Zhong; Yiqin Cheng; Bing Wang; Jingjing Wu; Meina Ye; Hongfeng Chen (Scientific Reports)
Abstract Non-puerperal mastitis (NPM) is an umbrella term for non-specific inflammatory mastitis that occurs during the non-puerperal period and has an unclear aetiology. The current study aims to characterize NPM patients and examine the determinants associated with NPM severity. This study analyzed the NPM inpatients admitted to the Department of Breast Surgery, Longhua Hospital Affiliated with the Shanghai University of Traditional Chinese Medicine from 2016 to 2020. We explored NPM patient characteristics through demographics, physical risks, lab tests, and medical history indicators. Multivariable logistic regression was conducted to identify the relationship between the prolactin (PRL) level and NPM severity stratified by breast structure. The majority of NPM inpatients had normal breast structures and were of lower average age than those with congenital nipple deformity (p = 0.002). Significant positive risk (p < 0.001) association between PRL level and NPM severity was observed among NPM inpatients with normal breast structure in both crude and adjusted models (adjusted OR: 2.91; 95%CI:1.88–4.52), with younger age as a protective factor (OR:0.94; 95%CI:0.91–0.97) and smoking history as a risk factor (OR:2.22; 95%CI:1.22–4.05). For NPM patients with nipple deformity, increasing odds of NPM severity regarding higher PRL level was observed while the result is not statistically significant at 0.05 level. (OR: 2.17; 95%CI: 0.94–5.03). The risk of NPM severe episodes is higher among patients with higher PRL levels, of which the association is stronger for NPM patients with normal breast structure, implying different pathogenesis between NPM patients with varied breast anatomy. Disagreement of the interaction effect testification indicates an improvement window for the current study. Trial registration: ChiCTR2000035929. Registered 20 August 2020(retrospectively registered).